Masto Knowledge System in Bajhang - Khati, Rajendra Bahadur (Journal of Jayaprithvi Multiple Campus, 2025)
The Masto tradition, deeply rooted in the cultural and spiritual life of the Khas people of Bajhang, Nepal, represents a unique and indigenous knowledge system that blends mythology, ritual practices, and community identity. This study explores the historical, spiritual, and socio-cultural significance of Masto regarded as the "God of Gods" and examines how it has shaped the local belief system and daily life of the Khas community. Using a qualitative auto/ethnographic approach within the interpretivist paradigm, the research draws on lived experiences, in-depth interviews, and literature to investigate the relevance and current status of Masto culture in Bajhang. The findings reveal a gradual disconnect between the younger generation and this rich heritage, exacerbated by its minimal representation in the formal school curriculum. The study argues for the urgent need to document, revitalize, and integrate the Masto tradition into local educational practices to preserve cultural identity and foster indigenous knowledge in education.